Cognitive View of Learning: Definition, Complexity and Problem Solving - Maulida Fitri; Neviyarni S; Herman Nirwana (Manajia: Journal of Education and Management, 2024)
The aim of this research is to study the cognitive view of learning. To achieve this goal, this research uses literature research or literature review methods. This research collects literature from various books and articles related to the subject discussed with the keywords cognitive view of learning. The research results show that the cognitive perspective in learning emphasizes interaction and mental processes in learning, where students manage information, experience emotional experiences, and become more independent by solving problems or using learning transfer to achieve learning goals. This approach can help students understand how to manage information, solve problems, and interact actively during the learning process.